Zoning of Nature Tourism Parks Based on Ecological and Socio-Economic Sensitivity: Case Study of Grojogan Sewu Nature Tourism Park - Evi Heriyaningtyas; Maryono Maryono; Fuad Muhammad (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Grojogan Sewu Nature Tourism Park, covering an area of 64,124 hectares, has undergone environmental and spatial changes that no longer align with its original management zoning plan. This study aims to redesign the management blocks based on ecological and socio-economic sensitivities through the use of spatial multi-criteria evaluation combined with a hierarchical decision-making process and geographic information system-based analysis. The objectives of the study are to determine management zones using ecological sensitivity criteria, including vegetation cover, land cover, slope classification, geological sensitivity, and distribution of flora and fauna. Additionally, socio-economic sensitivity is assessed using criteria such as accessibility to potential areas of utilization, zones of tourism activities, and water resource usage areas. The findings of this study indicate a revised spatial division of the nature park into two main management blocks: the protection block and the utilization block. The protection block accounts for approximately 36,966 hectares or 57.65 percent of the total area, while the utilization block comprises about 27,158 hectares or 42.35 percent. The proposed zoning scheme is expected to support effective conservation strategies and enhance integrated spatial planning for sustainable nature tourism management in Grojogan Sewu